PENGARUH KOMITMEN ORGANISASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA - Sunarno, 12.52.02.0263; Liliana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2015)
The  results of this study are the Influence of organizational commitment, organizational culture and job satisfaction on teacher performance. The research problems in this study are: (1) to examine  the influence of organizational commitment, school culture, and job satisfaction on teacher performance. (2) to test whether job satisfaction mediates organizational commitment, school culture of the teacher performance. The  samples of this study are 103 teachers of Kesatrian Senior High School under the Kesatrian Education Foundation in Semarang. The used sampling was census techniques and the used model was multiple regression analysis The results of this study are: (1) organizational commitment is not proved in influencing the job satisfaction, (2) school culture has positive and significant influence on the  job satisfaction, (3) organizational commitment was not proved in influence on teacher performance, (4) school culture has positive and significant influence on teacher performance, (5) the job satisfaction has  positive and significant influence on teacher performance, (6) job satisfaction variable is not proved having the function as intervening variable on the variable of school culture on teacher performance. Keywords: organizational commitment, school culture, job satisfaction, teacher performance